Determinants of quality of life among elderly patients with type 2 diabetes in northwest of iran: based on problem areas in diabetes - Moghaddam, Hamed Rezakhani; Sobhi, Eslam; Soola, Aghil Habibi (Frontiers in Endocrinology, 2022)
Background: Diabetes is a metabolic disease characterized by chronic hyperglycemia, leading to damage to various organs of the patients and reduce their life expectancy and quality of life. The aim of this study was to explore the determinants of quality of life based on the problem areas in diabetes. Methods: This cross-sectional study was carried out in an Iranian diabetic clinic in Ardabil. The problem areas in diabetes (PAID), the short form health survey (SF-12), and the socio-demographic questionnaire were all employed. Using the census sample method, 266 older people with type 2 diabetes from Ardabil's lone diabetic clinic took part in this study. One-way ANOVA, t-test, One-Sample Kolmogorov-Smirnov test, and multiple regression were used to analyze the data. Results: Data analysis showed that there was a statistically significant relationship between quality of life dimensions and PAIDs’ triple domains (p < 0.01). In the final model of predictors of quality of life, treatment barriers, psychological distress related to diabetes management, kind of treatment, age, and duration of diabetes were statistically significant predictors of the quality-of-life dimensions (p>0.05). Conclusion: Individual characteristics and factors connected to health services should be prioritized in any intervention program aimed at improving the quality of life of elderly diabetic patients. Psychological distress should be considered in addition to regular physician visits.